Can economic policy uncertainty and investors sentiment predict commodities returns and volatility? - Shahzad, Syed Jawad Hussain; Raza, Naveed; Balcilar, Mehmet; Ali, Sajid; Shahbaz, Muhammad (Elsevier Sci Ltd, 2017)
The objective of this paper is to employ the novel technique of nonparametric causality-in-quantiles to examine the predictability of returns and volatility of six important commodities over the weekly period July 1996 June 2016. We use a news-based measure of economic uncertainty, bullish and bearish investor sentiments and identify the structural breaks in commodities returns through modified Iterated Cumulative Sum of Squares (ICSS) algorithm; breaks render inference based on linear models less reliable. The results of our nonparametric causality-in-quantiles tests show that investors' sentiments (both bullish and bearish) have a causal impact, over the entire conditional distribution all most at all quantiles in both global financial crisis (GFC) and full sample, on the mean and variance of commodities returns which is also more profound compared to economic policy uncertainty (EPU). The commodity investors may include the general sentiments prevailing in equity markets in their information set while making investment decisions.
Keywords: Economic policy uncertainty; Investor sentiments; Commodities; Nonparametric causality